PS7:146 Investigation of chronic organ damage and disease outcome in hungarian lupus patients. (21st March 2018) - Tarr, T; Papp, G; Nagy, N; Zeher, M
Abstract : Introduction/objectives: Long-term survival of patients with systemic lupus erythematosus (SLE) improved worldwide, thus prevention of cumulative organ damage became a major goal in disease management. The aim of our study was to investigate the chronic organ damages and their influence on disease outcome in SLE. Method: We evaluated clinical conditions, laboratory findings and medications of 357 consecutive SLE patients, and assessed their impact on SLICC/ACR damage index (SDI) and disease outcome. Results: We detected one or more SDI scores in 77.87% of patients. Patients with disease duration of more than 10 years and subjects diagnosed at age above 40 had significantly higher SDI values. The most frequent damages were valvulopathies, cognitive dysfunction, angina pectoris and venous thrombosis. Higher cumulative glucocorticoid dose increased SDI, while chloroquin treatment was favourable for patients. Male gender, elevated SDI scores and higher cumulative doses of glucocorticoids increased mortality risk. Our data confirmed that disease duration, age at diagnosis, chronic high-dose glucocorticoid therapy have significant effects on the development of chronic organ damage. Higher SDI score is characterised with worse survival ratios. The most common chronic organ damages affected the cardiovascular or neuro-psychiatric system. Conclusions: As long-term survival in SLE improves, it becomes increasingly important to identify the determinants of chronic organ damage. Most of the chronic organ damage occurs in the cardiovascular and the neuropsychiatric systems, thus regular follow-up, screening and adequate therapy are essential for the best clinical outcome.